Towards better control and prevention of Rift Valley fever in the Greater Horn of Africa: a decision support tool for veterinary services - Jost, Christine; Sones, Keith R.; Bett, Bernard K.; Kihu, S.; Nzietchueng, S.; Njogu, G.; Swai, E.; Minjauw, B.; Amanfu, W.; Rocque, S. de la; Martin, V.; Mariner, Jeffrey C. (International Livestock Research Institute, 2009)
An outbreak of the viral zoonotic disease Rift Valley fever in East Africa in 2006/07 left more than 300 people dead and caused economic losses in Kenya alone estimated to exceed USD 30 million. Participatory studies undertaken shortly after the outbreaks abated enabled valuable lessons to be learned; if applied these lessons could significantly reduce the impact of future outbreaks. The lessons included the desirability of complementing and integrating international early warning systems with information from local people on the ground; the need for government-approved contingency plans and emergency funding arrangement to be in place; the need to initiate responses before the first human cases are detected; the difficulties of mounting effective livestock vaccination campaigns; and the need for clear, consistent and authoritative public health messages to be developed and tested well before an outbreak occurs. To address these issues, FAO and ILRI recently led a multi-stakeholder initiative to develop a decision support tool for the prevention and control of RVF in the Greater Horn of Africa. The tool is targeted at directors of veterinary services. The RVF outbreak is divided into a sequence made up of 12 key events: for each event a set of actions are listed that are considered appropriate at that stage. The tool is intended to facilitate timely, evidence-based decision-making that will enable RVF outbreaks to be better prevented or contained, thereby reducing the scale of impacts on lives and livelihoods as well as local, national and regional economies. In September 2008, FAO EMPRES warned that RVF could occur again in East Africa later that year. This early warning and the veterinary department’s reaction in Kenya, highlight two encouraging changes. First, the early warning was issued in September, two months earlier than in 2006. Second, the veterinary department immediately established an interdisciplinary, multistakeholder technical coordinating committee. Actions taken, informed by the new decision support tool for the prevention and control of RVF, included drafting of protocols for vaccination, livestock quarantine and vector control. The veterinary department had a limited stock of vaccine in hand, which it targeted to what it considered the highest risk areas. However, taking into consideration production and shipment delays, should these limited vaccination campaigns have had to be expanded it is unlikely that a sufficient level of population immunity from mass vaccination in high risk areas could have been achieved prior to mid-November, the time when suspected livestock cases were occurring in North Eastern Province in 2006. ILRI and partners are engaging in further research to determine what impacts the RVF Decision Support Tool had on Kenya’s 2008 response.